The Bioactive Effects of Chicoric Acid As a Functional Food Ingredient - Peng, Ye; Sun, Quancai; Park, Yeonhwa (Journal of medicinal food, 2019)
Chicoric acid, a hydroxycinnamic acid, has been reported to possess a variety of health benefits, including antivirus, antioxidant, anti-inflammation, obesity prevention, and neuroprotection effects. The purpose of this article is to summarize current knowledge of pharmacological and biological effects of chicoric acid. Since most studies to date on chicoric acid have limited their focus to cell cultures and animals, more human and mechanistic studies are therefore needed to further determine the beneficial effects of chicoric acid as a potential functional food ingredient.